Assessment of Evaluation of Tomato Seed Health and Sustainable Management Practices Using Biological and Chemical Approaches: Tomato Seed Health and Management - Naznin, Sadia; Kabir, Humayun; Chowdhury, Mahmudul Hasan; Hasan, Lutfol (SAARC Journal of Agriculture, 2025)
An experiment was conducted to evaluate the seed health status of tomato and their affectivity against fungal pathogens. The eight tomato varieties viz. Binatomato-6 (V1), Binatomato-7 (V2), Binatomato-10 (V3), Binatomato-11 (V4), Binatomato-12 (V5), Binatomato-13 (V6), Ratan (V7) and Roma VF (V8) and sixteen bio–agents and fungicide treatments viz. control (T0), Garlic (w/v) @ 1:1 (T1), 1:2 (T2), 1:3 (T3), Neem (w/v) @ 1:1 (T4), 1:2 (T5), 1:3 (T6), Allamonda (w/v) @ 1:1 (T7), 1:2 (T8), 1:3 (T9), Trichoderma sp. (w/v) @ 1:1 (T10), 1:2 (T11), 1:3 (T12), Sinkar (w/v) @ 1:1 (T13), 1:2 (T14) and 1:3 (T15) were used for the study. Results revealed that the apparently healthy seed was significantly highest (84.42%) in Binatomato-13 which showed the lowest discolored (3.32%) and deformed (3.02%) seed included the highest seed germination (93.0%), longest shoot (6.5 cm) and highest vigor index (1239.31). Six seed–borne fungi namely A. flavus, A. niger, F. oxysporum, C. lunata, Rhizopus sp and Penicillium sp. were identified where Ratan had highly susceptible (20.0%) and Binatomato-12 was the highly effective against the fungal incidence (7.64%) with highest mean incidence of A. flavus (3.18%) and lowest with Penicillium sp. (0.10%), incases of plant extracts, neem @ 1:1 w/v showed the highest vigor index (1433.20) which showed highest significant influenced on normal seedling (79.67%) and lowest abnormal seedling (9.67%) with reduced rate of dead (4.33) and hard (2.33%) seed. Application of neem @ 1:1 w/v also effective for the highest reduction of A. flavus (1.67%), F. oxysporum (0.60%), C. lunata (1.33%), R. stolonifer (1.0%) and Penicillium sp. (0.10%) while T3 (Garlic @ 1:3) was for A. niger (1.06). So, Binatomato-13 was the best qualitative variety while Neem @ (1:1) w/v was the proposing plant extract which have higher capability to reduce the seed borne infection. SAARC J. Agric., 22(2): 139-151 (2024)